Pengaruh Bentuk Baling-Baling Terhadap Kecepatan Putar Sebagai Media Pembelajaran - Ferdila, Ersi; Partono, Partono; Salim, M. Barkah (Universitas Muhammadiyah Metro, 2020)
ABSTRACTAnemometer propellers have many forms, but there is no data yet to show the difference between propeller and rotational speed. So the purpose of this study is to determine the difference in rotational speed based on the shape of the anemometer propeller.The research method used was experimental research. The experiments were carried out using fan blades, scissors, a quarter cup, and a turbine. Data analysis used the formula of rotational speed, accuracy, and error during the experiment.The results showed that each form of the propeller on the anemometer produced a different rotational speed. The shape of the propeller that produces the greatest speed is obtained from the shape of a quarter cup propeller with an estimated speed. The results of the study are used as learning resources in the form of posters. The poster created has been tested for eligibility by the design validator and material validtor. Keywords: Propeller, Rotational Speed.